Consumers' imperium : the global production of American domesticity, 1865-1920 - Hoganson, Kristin L. (University of North Carolina Press, 2007)
From curtains to clothing, from around-the-world parties to arts and crafts, this work presents different perspectives on the United States in the world by shifting attention from exports to imports, from production to consumption, and from men to women.